Tanshinone IIA potentiates the therapeutic efficacy of glucocorticoids in lipopolysaccharide-treated HEI-OC1 cells through modulation of the FOXP3/Nrf2 signaling pathway - Li Jie; Zhu Xiaoyan; Ye Shiming; Dong Qi; Hou Jie; Liu Jing; She Wandong (Acta Biochimica et Biophysica Sinica)
Glucocorticoids (GCs) are commonly used to treat sudden sensorineural hearing loss (SSNHL), although some patients are resistant to this therapeutic approach. Clinical studies have demonstrated the efficacy of tanshinone IIA (TA) in combination with GC for managing various human ailments. However, it remains unclear whether TA can mitigate GC resistance in SSNHL. Our aim is to elucidate the role of NRF2-induced transcriptional regulation of HDAC2 in influencing GC resistance and investigate the involvement of TA-related molecular pathways in GC resistance. Here, HEI-OC1 cells are treated with lipopolysaccharide (LPS) to establish an in vitro model for SSNHL. The cells are subsequently treated with dexamethasone (DXE) or DXE + TA. RT-qPCR and western blot analysis are used to measure the mRNA and protein levels of Forkhead box P3 (FOXP3), nuclear factor erythroid 2-related factor 2 (NRF2), and histone deacetylase 2 (HDAC2). Cell Counting Kit-8 (CCK-8) and 5-ethynyl-2’-deoxyuridine (EdU) assays are carried out to assess cell proliferation. Flow cytometry analysis is performed to evaluate apoptosis. Mechanistic studies involve chromatin immunoprecipitation (ChIP), luciferase reporter, and DNA pull-down assays. Our results show that treatment with TA + DEX significantly increases proliferation and suppresses apoptosis in LPS-treated HEI-treated OC1 cells. TA upregulates HDAC2 expression by activating NRF2-mediated transcription of HDAC2, with the NRF2-HDAC2 binding site located at bases 419–429 (ATGACACTCCA) in the promoter sequence of HDAC2. Furthermore, TA upregulates FOXP3 expression to activate NRF2 transcription, with the predicted FOXP3-binding site located at bases 864–870 (GCAAACA) in the promoter sequence of NRF2. In summary, these findings suggest that TA enhances the therapeutic effects of GC on the proliferation and apoptosis of HEI OC1 cells by increasing FOXP3/Nrf2 expression. These results indicate that TA may be promising for ameliorating GC resistance in patients with SSNHL.